Surface architecture of endospores of the Bacillus cereus/anthracis/thuringiensis family at the subnanometer scale - Kailas, Lekshmi (National Academy of Sciences, 2011)
Bacteria of the Bacillus cereus family form highly resistant spores, which in the case of the pathogen B. anthracis act as the agents of infection. The outermost layer, the exosporium, enveloping spores of the B. cereus family as well as a number of Clostridia, plays roles in spore adhesion, dissemination, targeting, and germination control. We have analyzed two naturally crystalline layers associated with the exosporium, one representing the “basal” layer to which the outermost spore layer (“hairy nap”) is attached, and the other likely representing a subsurface (“parasporal”) layer. We have used electron cryomicroscopy at a resolution of 0.8–0.6 nm and circular dichroism spectroscopic measurements to reveal a highly α-helical structure for both layers. The helices are assembled into 2D arrays of “cups” or “crowns.” High-resolution atomic force microscopy of the outermost layer showed that the open ends of these cups face the external environment and the highly immunogenic collagen-like fibrils of the hairy nap (BclA) are attached to this surface. Based on our findings, we present a molecular model for the spore surface and propose how this surface can act as a semipermeable barrier and a matrix for binding of molecules involved in defense, germination control, and other interactions of the spore with the environment.